PEMANFAATAN ZEOLIT PADA SUMUR RESAPAN AIR HUJAN UNTUK MENGURANGI RESIKO PENCEMARAN AIR TANAH AKIBAT LIMPASAN HUJAN UNTUK PENGEMBANGAN SNI 06-2459-2002 - Eko Winar Irianto (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
Groundwater recharge technology is the effort to reduce excessive surface runoff and to conserve thegroundwater as well. However, runoff can disperse the pollutants which then accumulate in water bodies.Hence, pollutants can contaminate the groundwater by polluted surface runoff that enters the absorption wellwhich is regarded as the most appropriate technology for water conservation. The objective of research is toknow the capability of zeolit absorbing pollutants accumulated in the surface runoff. A prototype ofabsorption well for conserving and minimizing the risk of groundwater contamination is proposed in thisresearch. Results of the research show that zeolit can reduce the pollutants dissolved in surface runoff. Thus,this material can be combined to the absorption well. This prototype should be built with local materials andwill be proposed to improve the specification of the absorption well registered in SNI 06-2459-2002.